Health-related quality of life among COVID-19 individuals: A cross-sectional study in Tamil Nadu, India - Suganya Barani; Tarun Bhatnagar; Meenakumari Natarajan; Kumari Gayathri; Harshal Bhimrao Sonekar; Akhil Sasidharan; T.S. Selvavinayagam; Bhavani Shankara Bagepally (Elsevier, 2022)
Introduction: The EQ-5D-5L questionnaire is a tool that is a very generic and preference-based instrument to describe the health-related quality of life. We have generated the stratified index utility value for the Tamil Nadu population and compared the utility values based on socio-demographic and clinical characteristics. Methods: We conducted a community-based analytical cross-sectional study using telephonic interviews from November 2020 till December 2020 among individuals aged 18 years and above who were infected by the coronavirus confirmed with an RT-PCR within 30 days in Tamil Nadu State. EQ-5D-5L profile, socio-demographic and clinical characteristics of the study participants were collected and analysed. Results: We interviewed 372 participants, with 57.5% were males, and their mean age was 44.5 ± 15.3 years. About 40% of participants reported as having comorbidities, such as diabetes (19.4%), hypertension (12.4%), heart disease (2.4%), kidney disease (0.8%) and others. The mean EQ-5D utility score was 0.925 ± 0.150, and the mean EQ-VAS was 90.68 ± 11.81. Overall, men had a higher utility value (0.938 ± 0.130) than women, (0.907 ± 0.170). Individuals with comorbidities, requiring longer hospitalisation were having lower utility scores than their counterparts. Conclusion: We report the EQ-5D-5L utility values for the COVID-19 illness. These values would help to estimate quality-adjusted life years in health economic evaluation studies.